Esophageal adenocarcinoma: risk factors and modern screening strategy - I. V. Mayev; D. N. Andreyev; Yu. A. Kucheryavy; M. P. Scheglanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present the modern concepts on epidemiological pattern and risk factors of esophageal adenocarcinoma (EAC) and analyze the modern screening approach. Summary. In developed countries EAC is characterized by rapid increase of mobidity, as well as by high mortality level. As a rule, EAC is diagnosed at the late stage: diagnosis is often made at the 3rd or 4th stage of the tumor that is a major contributing factor for high mortality as treatment options at these stages are significantly limited. The basic established risk factor for EAC is the gastroesophageal reflux disease (GERD). EAC develops usually as a complication of the Barret's esophagus (BE) being a consequence of the long-standing GERD. Male gender, Caucasian race, obesity and metabolic syndrome, tobacco smoking, and series of genetic markers are considered to be significant EAC risk factors. A main goal of EAC screening programs is the early diagnosis that allows to improve patient survival. Conclusion. Only GERD patients develop EAC, with the highest risk in males, Caucasians, smokers, overweight patients and those with uncontrolled symptoms. Timely diagnosis of GERD, its effective treatment and follow-up of BE cases can prevent EAC development.